2016
DOI: 10.1002/ird.1996
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Climate Change on Irrigated Agriculture in Southern Portugal

Abstract: Climate change projections point to increasing air temperature and reduced precipitation in southern Portugal, which would affect farming systems. This study aims to assess the impacts of climate change on irrigated agriculture in southern Portugal. These impacts were assessed by combining climate model data with a soil water balance model and a numerical model for the design of irrigation systems. Meteorological data from two weather stations were used along with three climate models (HadRM3P, HIRHAMh and HIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…A modeling study in major wheat growing regions of Australia suggested that variations in mean growing season temperature by ± 2°C could impose a substantial reduction on wheat grain production by up to 50% (Asseng et al 2011). Observed climate conditions in southern Portugal have shown a clear trend toward a more arid climate, with increased mean temperature and decreased annual precipitation, particularly spring precipitation (Páscoa et al 2017;Rolim et al 2017;Valverde et al 2015). The observed warming and drying trends are likely to be strengthened in future climates (Páscoa et al 2017;Rolim et al 2017), with a concomitant increase in the frequency and intensity of extreme weather events, e.g., droughts (Santos et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A modeling study in major wheat growing regions of Australia suggested that variations in mean growing season temperature by ± 2°C could impose a substantial reduction on wheat grain production by up to 50% (Asseng et al 2011). Observed climate conditions in southern Portugal have shown a clear trend toward a more arid climate, with increased mean temperature and decreased annual precipitation, particularly spring precipitation (Páscoa et al 2017;Rolim et al 2017;Valverde et al 2015). The observed warming and drying trends are likely to be strengthened in future climates (Páscoa et al 2017;Rolim et al 2017), with a concomitant increase in the frequency and intensity of extreme weather events, e.g., droughts (Santos et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on potential climate change influences on wheat production in Portugal were focused on either assessing crop water deficits (Rolim et al 2017) or using climate change projections without accounting for the potential changes in climate variabilities and associated extreme events (Valverde et al 2015). Besides, neither of these studies attempt to explore adaptation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In the province of Malaga RW is not yet used for agricultural irrigation. Using RW for irrigation purposes, in addition to savings of freshwater supplies, can partially supply some nutrients, particularly nitrogen, phosphorous, and potassium, which are the primary nutrients needed to stimulate yield and quality of agricultural crops [11]. Considering that RW may contain a high content of essential nutrients for plants, the use of this water to elaborate the irrigation solution could significantly reduce the application of standard commercial fertilizers and its associated costs.…”
Section: Membrane Reclamation Procedures Based On Ultrafiltration Andmentioning
confidence: 99%
“…However, the stationary assumption is being increasingly challenged by climate change (Milly et al, 2008;Li et al, 2017;Rolim et al, 2017;Yan et al, 2017a;Xu et al, 2018;Zhang et al, 2018). design rainfall) derived from the probability distribution of extreme rainfall, which is based on historical rainfall records and assumed to be stationary.…”
Section: Introductionmentioning
confidence: 99%
“…design rainfall) derived from the probability distribution of extreme rainfall, which is based on historical rainfall records and assumed to be stationary. However, the stationary assumption is being increasingly challenged by climate change (Milly et al, 2008;Li et al, 2017;Rolim et al, 2017;Yan et al, 2017a;Xu et al, 2018;Zhang et al, 2018). It is anticipated that the frequency and magnitude of extreme rainfall will increase due to global climate change (Intergovernmental Panel on Climate Change (IPCC), 2013).…”
Section: Introductionmentioning
confidence: 99%